Is ACT-Informed Exposure a Viable Treatment for Excoriation Disorder? A Multiple Baseline Study. Issue 1 (January 2023) - Thompson, Brian L.
This study piloted the use of ACT-informed exposure as an adjunct to habit reversal training (HRT) for excoriation disorder (ExD). Using a nonconcurrent multiple baseline single case design, four participants completed sessions of exposure and HRT. Repeated measures and self-report data were collected on skin picking and psychological flexibility. Two participants completed HRT followed by exposure, and two participants completed exposure followed by HRT. Results support the effectiveness of HRT in reducing picking. Results suggest exposure may have some impact in reducing picking, but effects were weaker compared to HRT. Contrary to predictions, repeated measures and self-report data did not indicate consistent improvement in psychological flexibility during exposure phases. As any reduction in picking may be clinically meaningful and all participants maintained gains at follow-up, there is some indication that exposure may be a second-line treatment worth further study. Limitations and future areas of research are discussed.